Vegetation richness and role in preserving avian biodiversity at City of Elmina Valley Central Park, Shah Alam, Selangor - Che Salim, Fatimah Az Zahra; Mohamed, Noralizawati; Bahari, Noraini (2025)
Amidst the urban hustle, birds silently contribute to the interconnectedness between cities and the natural world, playing pivotal roles in pest control, pollination, and seed dispersal. Serving as a bridge between communities and nature, birds offer therapeutic, recreational, and educational benefits. This study assesses Elmina Valley Central Park in Shah Alam, Selangor, focusing on its landscape design to preserve and enhance the local ecosystem, particularly for bird habitat and biodiversity. The park, a sustainable township by Sime Darby Developer, covers 42.4 acres and incorporates ecological principles. Utilizing qualitative methods, including tree and bird species identification, the study aims to identify plant categories, vegetation hierarchy, and species attracting bird communities. The research also analyzes the role of planting in preserving bird communities and overall biodiversity. Bird surveys, employing point counts and time survey methods, document species abundance and presence. Initial findings showcase the significance of vegetation diversity and structures in influencing bird habitat. The study provides valuable insights for enhancing urban parks as sanctuaries for avian biodiversity, fostering sustainable coexistence between wildlife and human development.